A virtual robot solution to support programming - Aparicio, J. T. (2019)
Computer programming is a valuable skill. But learning programming is sometimes difficult, time-consuming, even frustrating. In this context, there is a need for new approaches to help in the process of learning programming. Here it is presented a solution based on a virtual robot with progressive system and supported in a generic and portable language. Those features answer to some needs. First, the virtual robot allows for certain level tangibility to the results. Then, the implementation as a progressive system allows for the support of the learning process. Finally, the use of a generic and portable language allows for the installation of the system on many platforms.